Modified Glass Ionomer Cement with "Remove on Demand" Properties: An In Vitro Study - Shaza Bishti; Taskin Tuna; Garima Agrawal; Andrij Pich; Stefan Wolfart (MDPI AG, 2017)
Objectives: To investigate the influence of different temperatures on the compressive strength of glass ionomer cement (GIC) modified by the addition of silica-coated wax capsules; Material and Methods: Commercially-available GIC was modified by adding 10% silica-coated wax capsules. Test blocks were fabricated from pure cement (control) and modified cement (test), and stored in distilled water (37 °C/23 h). The compressive strength was determined using a universal testing machine under different temperatures (37 °C, 50 °C, and 60 °C). The maximum load to failure was recorded for each group. Fractured surfaces of selected test blocks were observed by scanning electron microscopy (SEM); Results: For the control group, the average compressive strength was 96.8 ± 11.8, 94.3 ± 5.7 and 72.5 ± 5.7 MPa for the temperatures 37 °C, 50 °C and 60 °C respectively. The test group reported compressive strength of 64.8 ± 5.4, 47.1 ± 5.4 and 33.4 ± 3.6 MPa at 37 °C, 50 °C and 60 °C, respectively. This represented a decrease of 28% in compressive strength with the increase in temperature from 37 °C to 50 °C and 45% from the 37 °C to the 60 °C group; Conclusion: GIC modified with 10% silica-coated wax capsules and temperature application show a distinct effect on the compressive strength of GIC. Considerable compressive strength reduction was detected if the temperature was above the melting temperature of the wax core.